The Potential of Architecture: The Meaning and Purpose of Commemorative Architecture in Islamic Civilizations - Pradhan, Natasha (AUC Knowledge Fountain, 2019)
I have always found places that seem to exist "out of time" so to speak, extremely peaceful and alluring. These could include cemeteries, or even monumental and out-of-time structures like the pyramids. Yet there is something even stronger one feels when inside such a structure. That is, when a space - architecture - has been created that allows one to not simply witness something that seems to exist in eternity, but to reside within it. One cannot divorce these structures - and the human desire to construct them - from religion and religiosity. For throughout time, commemorative architecture has played a big role in the religious practices of peoples. While no two examples of commemorative monuments from different cultures could be interpreted in precisely the same way, it is likely that both would reflect deep-seated beliefs, perhaps of a religious nature, of the culture in which they originated. In Islam, the concept and permissibility of commemorative architecture is fraught. Some interpretations even advocate for the destruction of such structures. This thesis looks at the universal concept of commemorative architecture and traces the emergence of the form in the Islamic tradition.